Succession Planning in Micro and Small Family Business (Case: Micro and Small Family Business in East Jakarta) - Sakti Hendra Pramudya (Universitas Airlangga, 2021)
Family business studies are gaining a foothold in Indonesia. This organization is the most common type of firm throughout the world. Nonetheless, the low survival rate of family businesses may relate to the issue of management succession and the issue is still the principal challenge that they need to face. This study will focus on knowing the importance of succession planning for family business owners, especially those belonging to the micro and small business category. The study involved one hundred family business owners in East Jakarta as respondents of the survey. The study itself would be focused on the ground rules made by the incumbents during succession planning. The study has revealed that, generally, the majority of the sample does not have an appropriate plan of succession. The result also exhibits that the majority of respondents favoring nuclear family members as the future successor. Moreover, the homosocial reproduction phenomenon also could be identified from the survey.